Genome-Wide Association Analysis Reveals Key Genes Responsible for Egg Production of Lion Head Goose - Zhao, Qiqi; Chen, Junpeng; Zhang, Xinheng; Xu, Zhouyi; Lin, Zhenping; Li, Hongxin; Lin, Wencheng; Xie, Qingmei (Frontiers in Genetics, 2020)
The lion head goose is one of the most important agricultural resources in China; however, its breeding process is relatively slow. In the present study, a genome wide association study was performed for the genetic selection of egg production characters in lion head geese. We detected 30 single nucleotide polymorphisms located in or near 30 genes that might be associated with egg production character and quantitative real-time polymerase chain reaction was used to verify their expression level in lion head geese. The results showed that the expression levels of CRTC1 (encoding CREB-regulated transcription coactivator 1), FAAH2 (encoding Fatty acid amide hydrolase 2), GPC3 (encoding Glypican 3), and SERPINC1 (encoding Serpin family C member 1) in high egg production population were significantly lower than those in the low egg production populations (*P < 0.05). The expression levels of CLPB (encoding Caseinolytic peptidase B protein homolog), GNA12 (encoding Guanine nucleotide-binding protein subunit alpha-12), and ZMAT5 (encoding Zinc Finger, Matrin Type 5) in the high egg production population were significantly higher than those in the low egg production populations (*P < 0.05). The expression of BMP4 (encoding Bone morphogenetic protein 4), FRMPD3 (encoding FERM and PDZ domain containing 3), LIF (encoding Leukemia inhibitory factor), and NFYC (encoding Nuclear transcription factor Y subunit gamma) in the high egg production population were very significantly lower than those in the low egg production population (**P < 0.01). Our findings provide an insight into the economic traits of lion head goose. These candidate genes might be valuable for future breeding improvement.